2018
DOI: 10.1002/ejsp.2365
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative intergroup contact: Interaction not asymmetry

Abstract: This research reports a novel investigation into the comparative effects of positive and negative direct and extended intergroup contact on intergroup orientations. It tested the generality of the positive–negative asymmetry effect among majority (N = 357) and minority (N = 101) group members in Iceland. Little evidence of asymmetry was observed: the beneficial effects of positive contact were mostly as strong as the detrimental effects of negative contact, for both direct and extended contact. However, eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 38 publications
9
91
3
Order By: Relevance
“…Additionally, and in line with the rejection-identification model (Branscombe et al, 1999), there are crossgroup relationships such as that negative majority group contact is positively associated with minority and religious group identification. However, our results are in line with recent studies, which found equal or stronger effects of positive contact compared to negative contact (for a discussion, see Arnad ottir, Lolliot, Brown, & Hewstone, 2018). Our findings suggest that regarding both groups the total effect of positive contact on identification with the respective group and the acculturation attitude toward it is much stronger than the total effect of negative contact.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, and in line with the rejection-identification model (Branscombe et al, 1999), there are crossgroup relationships such as that negative majority group contact is positively associated with minority and religious group identification. However, our results are in line with recent studies, which found equal or stronger effects of positive contact compared to negative contact (for a discussion, see Arnad ottir, Lolliot, Brown, & Hewstone, 2018). Our findings suggest that regarding both groups the total effect of positive contact on identification with the respective group and the acculturation attitude toward it is much stronger than the total effect of negative contact.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…This finding contradicts the positive-negative contact asymmetry hypothesis, which states that negative contact with members of a group has stronger effects on intergroup attitudes toward the group, because negative contact experiences are assumed to heighten category salience more than positive contact (e.g., Barlow et al, 2012). However, our results are in line with recent studies, which found equal or stronger effects of positive contact compared to negative contact (for a discussion, see Arnad ottir, Lolliot, Brown, & Hewstone, 2018). Moreover, the original positive-negative contact asymmetry hypothesis was formulated with regard to effects of contact on intergroup attitudes.…”
Section: Theoretical Implicationscontrasting
confidence: 60%
“…Recent advances in the social perception literature suggest that all three components affected by intergroup contact – intergroup cognition, affect, and behaviours – are systematically linked, producing outgroup‐specific patterns of prejudice (Cuddy et al ., ). While some researchers combined different measures of cognitive, affective and/or behavioural measures within one study as different outcomes (see, e.g., Aberson, ; Árnadóttir, Lolliot, Brown, & Hewstone, ; Schäfer, Kros, et al ., ), and showed differential reactions to outgroups (e.g., Abrams & Houston, ), intergroup contact effects have been rarely linked to integrative models of social perception (but see, e.g., Brambilla, Hewstone, & Colucci, ; Brambilla, Ravenna, & Hewstone, ; Cameron, Rutland, Turner, Holman‐Nicolas, & Powell, ; Listiani et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, consider a German survey‐based study conducted in 2017 (Seidler, ), when a majority of Germans felt that refugees disrupted their way of life (Infratest dimap, ); in this threat‐ridden context, negative contact emerged as a stronger and more powerful predictor of prejudice toward refugees, relative to the effects of positive contact (Seidler, ). However, findings regarding this difference in magnitude are far from consistent across studies (see, e.g., Aberson & Gaffney, ; Árnadóttir, Lolliot, Brown, & Hewstone, ; Kotzur & Wagner, )…”
Section: Considering the Joint Effects Of Positive And Negative Contactmentioning
confidence: 98%